Structural behaviour of precast concrete sandwich panel with high thermal efficiency - Bida, Sani Mohammed (2018)
Malaysian Government has targeted the year 2020 for full implementation for energy efficiency in buildings known as Green Building. In line with this perspective, this research aims to develop a thermally efficient and structurally acceptable precast concrete sandwich panels (PCSP) for structural applications. In order to achieve the aims, four objectives are outlined to determine the thermal and structural performance of staggered shear connectors. The staggered shear connector is a method used to avoid thermal bridges between layers. In this research, PCSP is designed with staggered shear connection spaced at 200, 300 and 400 mm on each concrete layers. While the control panel is designed with a direct shear connection at 200 mm. Four panels of 500mm x 500mm and 150mm thick are subjected to Hot Box Test to determine the thermal performance. While for structural performance, four (4) number of a full-scale panel of size 2500mm x 1650mm x 150mm are subjected to flexural test and another four (4) of 3000mm x 1650mm x 150mm size for axial load tests. These experimental results are validated by numerical analysis using the finite element method (FEM). In addition, an empirical equation of axial load capacity of the reinforced concrete wall was modified to determine the PCSP capacity. The hot box test result shows that thermal efficiency of the PCSP with staggered shear connectors increases with increase in spacing. The PCSP with 400 mm staggered shear connectors indicate the best thermal efficiency with a thermal resistance (R-value) of 2.48 m²K/W. The R-value is higher than the maximum value recorded in the literature. The thermal performance was verified by FEA which shows less than 5% error coupled with a precise prediction of isothermal flux lines behaviour. The structural performance of PCSP under flexural loading showed that all PCSP with staggered shear connector achieved full compositeness with no debonding failure observed. The PCSP panel with a staggered shear connector at 300mm is capable of sustaining the axial capacity for five (5) storey load. However, beyond 300 mm staggered shear connector, the PCSP failed due to bucking. The experimental results were verified by FEA with about 4% and 15% error for the flexural and axial loadings, respectively. The empirical equation of axial load capacity of the reinforced concrete wall has overestimated the ultimate load capacity of PCSP. Therefore, the equation is subjected to statistical analysis using particle swarm optimization technique (PSO) by taking into consideration the effect of insulation and shear connection in PCSP. The modified equation has successfully predicted load capacity of PCSP with high accuracy. The result was achieved with objective function (MAE) at swarm 30 with minimum iteration and CoV value of 10%. In conclusion, the PCSP with 300mm staggered shear connectors has met the energy efficiency requirement for sustainable buildings i.e. thermally efficient with excellent structural performance in both axial and flexural behaviour. These results proved that better thermal resistant and structural performance of PCSP can be achieved using conventional steel and concrete materials using staggered thermal path approach. Hopefully, the output of this research will help designers; both architects and engineers to choose PCSP wall to provide better thermal resistance and load bearing structural panels toward green and sustainable buildings.